PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PROSTITUSI ONLINE MELALUI APLIKASI MICHAT - Bahari, Roni; Yuspin, Wardah (Media Keadilan: Jurnal Ilmu Hukum, 2023)
The enforcement of online prostitution laws against sexual service providers or prostitutes on the MiChat application which have not been strictly regulated in the laws and regulations in Indonesia and also criminal sanctions have not been able to create a deterrent effect for the perpetrators. This study aims to find out how law enforcement is carried out against online prostitution performed by PSK through the MiChat application. The research method used is normative legal research using statutory approaches, conceptual approaches, and case approaches. The research results show that online prostitution through the MiChat application is happening in various ways and its modus operandi, law enforcement against online prostitution through the MiChat application influenced by several factors including legal factors that have not explicitly regulated sex workers, law enforcement factors that have their respective roles in enforcing prostitution laws online less qualified in the field of information technology, inadequate facilities and infrastructure, and social and cultural factors that are still indifferent and do not care about this criminal act of prostitution.Keywords: Law Enforcement, Online Prostitution, PSK, MiChat Application